Influence Of Acidic Calcium Phosphate Solution Concentration On The Properties Of Dicalcium Phosphate Dihydrate Coated On Β-Tricalcium Phosphate Pellets - Abidin, Nurul Zawani Zainal (2019)
The aim of this study is to investigate the effect of acidic calcium phosphate solution concentration in fabricating dicalcium phosphate dihydrate (DCPD) coated on β-TCP pellets. β-TCP pellets were exposed to an acidic calcium phosphate solution for 1, 3 and 5 hours in order to obtain DCPD-coated layer on β-TCP pellets through dissolution-precipitation reaction. Several characterization methods such as X-Ray Diffraction (XRD), Fourier-Transform Infrared Spectroscopy (FTIR), Scanning Electron Microscope (SEM), Atomic Force Microscope (AFM), porosity analysis and compression test were carried out on specimen. The analyses of XRD and SEM showed that the amount of DCPD crystal precipitated on the pellets were increased when increasing the acidic calcium phosphate solution concentration. Increasing the amount of DCPD formation will reduced the porosity until 20% and increased the mechanical strength of specimen up to 40%. Meanwhile, XRD and SEM analyses showed that hydroxyapatite (HAp) formation were increased after increasing the soaking time of β-TCP pellet treated for 3 hours using different concentration of acidic calcium phosphate solution in Hank’s Balanced Salt Solution (HBSS). Therefore, based on this study shows that the amount of DCPD coated on β-TCP pellet could be regulated by changing the concentration of acidic calcium phosphate solution that induced HAp formation at physiological body condition.